Pengaruh Aksesibilitas Unit Lost And Found terhadap Kepuasan Penumpang PT. Gapura Angkasa di Bandar Udara Sultan Thaha Syaifuddin Jambi - Siti Nur Cahyanti; Yunus Purnama (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Accessibility of lost and found units has a significant effect on passenger experience and their perception of airport services. In situations of lost or left behind items, passenger satisfaction is influenced by ease of access to services, including strategic location, clarity of information, and efficiency of reporting and retrieval processes. This study aims to measure the effect of accessibility of lost and found units on passenger satisfaction and the level of satisfaction at PT Gapura Angkasa, Sultan Thaha Saifuddin Jambi Airport, using the Customer Satisfaction Index (CSI) method. This quantitative study took place from August 1 to September 30, 2024, with a population of around 45 passengers per month. The sample consisted of passengers aged at least 17 years who used the lost and found services of Garuda Indonesia and Citilink airlines. Data collection techniques were carried out through the distribution of questionnaires and surveys. This study found that the t-test showed a significance of 0.002 <0.05 and t count 3.292> t table 2.024, so the alternative hypothesis (Ha) was accepted. This means that there is a positive influence between the accessibility of lost and found units and passenger satisfaction of PT Gapura Angkasa at Sultan Thaha Syaifuddin Airport, Jambi; the better the accessibility, the higher the passenger satisfaction. The level of passenger satisfaction was recorded as very high, with a Customer Satisfaction Index (CSI) of 97.45%. However, there needs to be improvement in several aspects, such as the activeness of information officers, ease of reporting procedures, and the number of staff, to maintain service quality and improve passenger satisfaction.